New Media in Environmental Communication: A Study on CIFOR (The Center for International Forestry Research) - Pradipta Dirgantara; Abdul Fadli Kalaloi; Indria Angga Dianita (Jurnal Ilmu Lingkungan, 2024)
Nowadays new media is widely used not only for entertainment purposes, but also to raise public awareness about major environmental issues which is critical for presenting topics like climate change, global warming, and deforestation, as well as encouraging public debate and information exchange. This research aims to seek the utilization of new media in environmental communication. Environmental communication extends beyond campaign-related activities which also affects how people see themselves and the natural world around them. This research uses CIFOR (The Center for International Forestry Research) as a study case because it is recognized as an internationally non-profit scientific organization that carries out research on the most important issues in global forest and landscape management. This research benefits from Ecological Model of the Communication Process which employs qualitative research method with single instrumental case study approach. Data is gathered through direct observation, semi-structured interviews, and extensive literary study. The result demonstrates that CIFOR has been developing multiple digital channels including podcasts, videos, datasets, presentations, and datasets. This is in accordance with the Ecological Model of the Communication Process to communicate their findings. Additionally, it has been found that new media in CIFOR combines and blurs the lines between interpersonal communication and mass media communication.